PENGARUH FLASH SALE DAN GRATIS ONGKIR TERHADAP KEPUTUSAN PEMBELIAN DENGAN IMPLUSE BUYING SEBAGAI VARIABLE MEDIASI PADA MAHASISWA - Manullang, Wintasya; Amellia Putri , Cindy; Ain Nisrina , Hawarul; Gabryela Br. Simatupang , Putri; Hasyim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of flash sales and free shipping on purchase decisions with impulse buying as a mediating variable among university students. The rapid growth of e-commerce platforms has encouraged the use of various promotional strategies, such as flash sales and free shipping, which are considered effective in influencing consumer behavior, especially students who tend to be responsive to limited-time offers and price incentives. This study employs a quantitative approach using a survey method through questionnaires distributed to 112 student respondents. Data analysis techniques include descriptive and inferential analysis to examine the relationships between variables and the mediating role of impulse buying. The results indicate that flash sales and free shipping have a positive effect on purchase decisions and significantly increase the tendency of impulse buying, which in turn strengthens purchase decisions. Impulse buying is proven to act as a mediating variable in the relationship between flash sales and free shipping on purchase decisions. These findings suggest that time- limited promotional strategies and price incentives are effective in encouraging spontaneous purchases and enhancing consumer purchase decisions.